Female obesity does not impact live birth rate after frozen-thawed blastocyst transfer. Issue 4 (13th March 2020) - Prost, E; Reignier, A; Leperlier, F; Caillet, P; Barrière, P; Fréour, T; Lefebvre, T
Abstract: STUDY QUESTION: Does female obesity affect live birth rate after frozen-thawed blastocyst transfer? SUMMARY ANSWER: Live birth rate was not statistically different between obese and normal weight patients after frozen-thawed blastocyst transfer (FBT). WHAT IS KNOWN ALREADY: Obesity is a major health problem across the world, especially in women of reproductive age. It impacts both spontaneous fertility and clinical outcomes after assisted reproductive technology. However, the respective impact of female obesity on oocyte quality and endometrial receptivity remains unclear. While several studies showed that live birth rate was decreased in obese women after fresh embryo transfer in IVF cycle, only two studies have evaluated the effects of female body mass index (BMI) on pregnancy outcomes after frozen-thawed blastocyst transfer (FBT), reporting conflicting data. STUDY DESIGN, SIZE, DURATION: This retrospective case control study was conducted in all consecutive frozen-thawed autologous blastocyst transfer (FBT) cycles conducted between 2012 and 2017 in a single university-based centre. A total of 1415 FBT cycles performed in normal weight women (BMI = 18.5–24.9 kg/m 2 ) and 252 FBT cycles performed in obese women (BMI ≥ 30 kg/m 2 ) were included in the analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: Endometrial preparation was standard and based on hormonal replacement therapy. One or two blastocysts were transferred according to couple's history and embryo quality. MAIN RESULTS AND THE ROLE OF CHANCE: Female and male age, smoking status, basal AMH level and type of infertility were comparable in obese and normal weight groups. Concerning FBT cycles, the duration of hormonal treatment, the stage and number of embryos (84% single blastocyst transfer and 16% double blastocysts transfer) used for transfer were comparable between both groups. Mean endometrium thickness was significantly higher in obese than in normal weight group (8.7 ± 1.8 vs 8.1 ± 1.6 mm, P  < 0.0001). Concerning FBT cycle outcomes, implantation rate, clinical pregnancy rate and live birth rate were comparable in obese and in normal weight groups. Odds ratio (OR) demonstrated no association between live birth rate after FBT and female BMI (OR = 0.92, CI 0.61–1.38, P  = 0.68). LIMITATIONS, REASONS FOR CAUTION: Anthropometric parameters such as hip to waist ratio were not used. Polycystic ovarian syndrome status was not included in the analysis. WIDER IMPLICATIONS OF THE FINDINGS: Our study showed that live birth rate after frozen-thawed blastocyst transfer was not statistically different in obese and in normal-weight women. Although this needs confirmation, this suggests that the impairment of uterine receptivity observed in obese women after fresh embryo transfer might be associated with ovarian stimulation and its hormonal perturbations rather than with oocyte/embryo quality. STUDY FUNDING/COMPETING INTEREST(S): No external funding was received. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.